Uncovering the pharmacology of Ginkgo biloba folium in the cell-type-specific targets of Parkinson’s disease - Yan, Yu-Chen; Xu, Zhi-Heng; Wang, Jian; Yu, Wen-Bo (Frontiers in Pharmacology, 2022)
Parkinson's disease (PD) is the second most common neurodegenerative disease with a fast-growing prevalence. Developing disease-modifying therapies for PD remains an enormous challenge. Current drug treatment will lose efficacy and bring about severe side effects as the disease progresses. Extracts from Ginkgo biloba folium (GBF) have been shown neuroprotective in PD models. However, the complex GBF extracts twingled with complicated PD targets hinder further drug development. In this study, we have pioneered the use of single-nuclei RNA sequencing data in network pharmacology analysis. Furthermore, high-throughput screening for potent drug-target-interaction (DTI) was conducted with the aid of a deep learning algorithm, DeepPurpose. The strongest DTIs between ginkgolides and MAPK14 were further validated by molecular docking. This work should help to advance the procedure of network pharmacology analysis, in order to tackle the limitation of conventional researches. Meanwhile, these results should contribute to a better understanding of the complicated mechanisms of GBF in treating PD and lay the theoretical ground for future drug development in PD.